Keefektifan Model Jaring Hubungan Makna Kata dalam Pembelajaran Kosakata di Sekolah Dasar - Winihasih Winihasih (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
The Effectiveness of Semantic-Mapping Model in Vocabulary Learning at Elementary School. The study aimed to find out whether semantic-mapping model was an effective learning model in learning vocabulary at elementary school. A quasi experimental design was employed, involving experimental and control groups. The data in the form of scores of pretest and posttest of the two groups were analyzed using t-test. The results indicate that the proposed model is more effective than the traditional one in vocabulary learning.